Dry reforming for glycerol hydrogen-rich production over Ni/CaO, Ni/ZrO2 and 5%Re-Ni/CaO - Nur Nabillah, Mohd Arif (2017)
Increase in biodiesel production has lead towards a glut production of glycerol where it is estimated that 3 megatons of crude glycerol will be produced by 2020. This leads towards oversupply crisis of glycerol and simultaneously influences its market price. Conversion of glycerol into hydrogen via dry reforming is a potential alternative to overcome this crisis which helps to overcome the environmental problems related with the greenhouse gases production. This work focused on the feasibility of glycerol dry reforming over a series of synthesised catalysts. In this work, nickel was supported with different oxides namely calcium oxide and zirconium oxide. The best oxide support was then promoted with rhenium via wet impregnation technique. The reaction was conducted in a stainless-steel fixed bed reactor at various temperatures of 600–900 °C, carbon dioxide to glycerol ratios of 1, 3, and 5, and gas-hourly space velocity (GHSV) of 7.20 × 104 to 1.44 × 104 mL gcat-1 h-1. The physichochemical characterisations of the catalysts were analysed using X-ray diffraction (XRD), scanning electron microscopy (SEM), nitrogen physisorption, temperature programmed calcination (TPC), temperature-programmed oxidation (TPO), and field emission scanning microscopy/energy dispersive X-ray analysis (FESEM-EDX). In the screening stage, the Ni/oxide support loadings were varied and carried out at a fixed reaction condition of T (700 °C), CGR (1), and GHSV (3.6 × 104 mL gcat-1 h-1). Based on the screening study, 15%Ni/CaO exhibited smaller crystallite size that leads to well dispersion of NiO and high catalysts specific surface area. In TPD-NH3 analysis, 15%Ni/CaO possessed greater basic site concentration that helped in suppressing the carbon deposition. In the reaction study, this catalyst achieved 32.33% of glycerol conversion and 28.83% of hydrogen yield. After selecting the best catalyst support, the properties of the catalyst was enhanced with the addition of 5%Re as the catalyst promoter. For 5%Re-Ni/CaO catalyst, the crystallite size was found to be small within the range of 0.49 to 0.90 nm. This condition has significantly reduced the specific surface area of the catalyst due to the partial blockage of catalyst support. Besides that, Re promotion also helped to speed up the reduction of NiO to Ni and increased the acid site of catalyst. This condition has improved the catalytic activity of the promoted catalyst up to 44% of glycerol conversion. From the reaction study, the highest glycerol conversion and hydrogen yield were successfully achieved at the temperature of 800 °C and GHSV of 1.44 × 104 mL gcat-1 h-1 with CGR of 1 for non-promoted catalyst and CGR of 3 for promoted catalyst. It is determined that hydrogen gas was majorly produced from glycerol decomposition and indirectly from water gas shift reaction. Increment of temperature and GHSV beyond the optimum point is not beneficial due to the CO2 hydrogenation and methanation processes that built up of carbon deposition on the surface of catalyst. The formation of whisker carbon for both catalysts is proven in FESEM-EDX and TPO analysis.